Grape Rootstock Response to Salinity, Water and Combined Salinity and Water Stresses - Donald L. Suarez (Agronomy, 2019)
Diminishing availability of non-saline water in arid and semiarid regions is of concern to all irrigated agricultural producers, including wine and grape producers. Grapes are not a salt tolerant crop and producers often face the choice of either limiting fresh water application, using alternative saline waters or a combination of both. We examined the salt tolerance and effect of restricted water application on three purported salt tolerant rootstocks grafted to Cabernet Sauvignon scion in a 4-year replicated field experiment. ANOVA indicated significant effects of salinity water stress and rootstock on fruit yields. The 140 Ruggeri scion was the top producer across all treatments including control, followed by Salt Creek, with St. George significantly less productive than 140 Ruggeri across all treatments. In terms of salt tolerance, Salt Creek and 140 Ruggeri were not statistically different but St. George was significantly less tolerant than Salt Creek. In terms of drought tolerance (relative yield), there were no statistical differences among rootstocks. Soil salinity profiles and soil moisture sensors indicated reduced water consumption under high salinity, thus no matric stress under 60% of optimal water application when high salt stress was present. The multiplicative stress model where salt and water stress are individually evaluated did not satisfactorily predict yield under combined salinity and reduced water application, likely due to decreased water consumption under saline conditions. Short term (one year) experiments underestimate salt damage to grape vines as salt tolerance decreased over the 4-year experiment.